WAYS OF ENSURING SOCIAL RESPONSIBILITY OF ARCHITECTURAL AND CONSTRUCTION COMPANIES: ECONOMIC BENEFITS AND FURTHER DEVELOPMENT VECTORS - YASHCHENKO, Oleksii; KUBANOV, Ruslan; PRUSOV, Dmitry; MAKATORA, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the study of the ways to ensure the social responsibility of architectural and construction companies and to the assessment of the economic benefits associated with the implementation of such practices. The authors note that the social responsibility of business, including the construction industry, is becoming increasingly important in the modern world. This is driven by increasing public awareness of the impact of human activity on the environment and society at large. Architects and builders should therefore consider the environment, safety and comfort of users and interact with local communities, as well as fulfilling their professional duties. Improving corporate reputation, attracting and retaining talented people, increasing market competitiveness and ensuring sustainable development have been identified as the main benefits of implementing social responsibility. It can also help attract investment and partnerships with government and non-government organisations by achieving high standards of social responsibility. The study details the main areas of social responsibility in the activities of architectural and construction companies. These include socio-cultural and environmental considerations and active engagement with local communities to ensure the safety and comfort of building occupants. The importance of the reduction of negative impacts on the environment through the use of innovative technologies, environmentally friendly materials, energy efficient solutions, etc. is also underlined. Improved image and reputation, increased consumer confidence, attracting new clients and partners, and increased productivity and efficiency are some of the economic benefits of social responsibility for architectural and construction companies. The authors emphasise that socially responsible business is becoming a key factor in succeeding in today’s environment. Active cooperation with the public, government agencies and research organisations is essential for the further development of architectural and construction companies on the basis of social responsibility. In this way it will be possible to develop and implement innovative approaches aimed at ensuring sustainable development and improving the standard of living of the population. In general, the study shows that integrating socially responsible practices into the activities of architectural and construction companies contributes not only to effective risk management and improving the quality of work, but also to creating a positive image of the company, attracting new clients and maintaining a stable position in the market.